Serviço Social e debate étnico-racial: uma análise dos projetos político-pedagógicos de cursos – PPC das unidades de formação acadêmica – UFA em serviço social da região norte da ABEPSS - Silva, Kallynne Guimarães da (Universidade Federal do Tocantins, 2023)
This Course Completion Work aims to analyze the Course Pedagogical Projects - PPC, with regard to the ethnic-racial debate in professional training in Social Work of the Federal Academic Training Units - UFA of the northern region, following the regional division of Association for Teaching and Research in Social Work – ABEPSS, so the Social Work courses chosen for this study are from the Federal Universities of Maranhão, Tocantins, Amazonas, Pará and Piauí. The proposal of qualitative analysis is developed around verifying how the UFA present the ethnic-racial debate in the training in Social Work in the northern region. The interest in the theme for this work develops from concerns about professional practice, considering that, due to the Brazilian social and cultural formation, the ethnic-racial discussion in society, as well as in-service training, was not placed on the agenda. society for many years. In this sense, contemporaneity comes with a lack of theoretical and critical discussions on the ethnic-racial issue, within the profession of social work, posing several challenges for the understanding of the demands that reach the socio-occupational spaces of the profession, which require the understanding of social class, race/ethnicity, and gender, in which without this understanding the understanding of the expressions of the 'social question', are limited.